ウミタカマル ヲ モチイタ ナンキョク ケンキュウ ワークショップ 2008 ホウコク - 笠松, 伸江; カサマツ, ノブエ; 堀本, 奈穂; ホリモト, ナホ; 茂木, 正人; モテキ, マサト; 高橋, 邦夫; タカハシ, クニオ; 長田, 和雄; オサダ, カズオ; 平譯, 享; ヒラワケ, トオル; et al. (情報・システム研究機構国立極地研究所, 2008)
P(論文) 「海鷹丸を用いた南極研究ワークショップ2008」を東京海洋大学品川キャンパスにおいて2008年8月8日に開催した.参加者は36名であった.2002/03年,2004/05年,2005/06年,2007/08年シーズンに行われた東京海洋大学「海鷹丸」の南極海研究航海(それぞれ,UM0203,UM0405,UM0506,UM0708航海)で得られた結果が報告された後,得られたデータやサンプルの管理及び成果取りまとめについて議論した. A workshop "Southern Ocean Study by RT/V (research and training vessel) Umitaka-Maru, 2008" was held on 8th August 2008 at the Shinagawa Campus of the Tokyo University of Marine Science and Technology (TUMSAT), with 36 participants. Results obtained during RT/V Umitaka-Maru (TUMSAT) cruises in austral summer of 2002/03 (UM0203), 2004/05 (UM0405), 2005/06 (UM0506), and 2007/08 (UM0708) and the current status of data were reported. Data management and synthesis of scientific results were discussed. departmental bulletin paper